Job satisfaction and its associated factors of preventive medicine workers in northern Vietnam - Nguyen Quynh, Anh; Nguyen Thu, Ha; Tran Anh, Dung (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: To access job satisfaction and its associated factors of preventive medicine workers in Vietnam. Method: A cross-sectional study was conducted using a purposive convenience sample of 12 preventive medicine centers in three provinces of northern Vietnam. Overall, 400 preventive medicine staff were invited to participate, and a response rate of 95.7% was percieved (153 from three provincial centers and 230 from nine district centers). All eligible participants completed the six-point response and validated questionnaire, which included questions relating to general information (basic demographics and social circumstances), job satisfaction. The job satisfaction measure produced scores for individual facets and overall job satisfaction (scored as continuous variables). Result: Bivariate analyses showed that satisfaction with pay and benefits had the lowest mean score (Mean: 3.81, SD: 0.76), satisfaction with the nature of the job had the highest mean score (Mean: 4.81, SD: 0.56), while the mean score of overall job satisfaction was 4.36, SD: 0.50. Bivariate analysis showed that personal factors were significantly associated with the facets of job satisfaction and overall job satisfaction. However, these associations varied across facets. Satisfaction with pay and benefits was significantly associated with six personal factors, including age, marital status, number of children, having a second job, tenure at the current job, and length of employment at the current center, while no personal factors were significantly associated with satisfaction with community support. Conclusion: The findings regarding the factors that appear to influence satisfaction could be useful to help management at preventive medicine centers and policy makers design programs to improve morale and commitment among these workers. Addressing the aspects of job satisfaction that were found to have the lowest scores may help the preventive medicine system to retain staff.